Accuracy of galactomannan testing on tracheal aspirates in COVID‐19‐associated pulmonary aspergillosis. Issue 4 (13th February 2021) - Roman‐Montes, Carla M.; Martinez‐Gamboa, Areli; Diaz‐Lomelí, Paulette; Cervantes‐Sanchez, Axel; Rangel‐Cordero, Andrea; Sifuentes‐Osornio, Jose; Ponce‐de‐Leon, Alfredo; Gonzalez‐Lara, Maria F.
Abstract: Objective: Our aim was to evaluate the performance of two galactomannan (GM) assays (Platelia Aspergillus EIA, Bio‐Rad ®, and Aspergillus GM LFA, IMMY ® ) in tracheal aspirate (TA) samples of consecutive critically ill patients with COVID‐19. Methods: We included critically ill patients, performed GM‐EIA and GM‐Lateral Flow Assay (GM‐LFA) in TA and followed them until development of COVID‐19‐associated pulmonary aspergillosis (CAPA) or alternate diagnosis. CAPA was defined according to the modified AspICU criteria in patients with SARS‐CoV‐2 infection. We estimated sensitivity, specificity, positive and negative predictive values for GM‐EIA, GM‐LFA, the combination of both or either positive results for GM‐EIA and GM‐LFA. We explored accuracy using different breakpoints, through ROC analysis and Youden index to identify the optimal cut‐offs. We described antifungal treatment and 30‐day mortality. Results: We identified 14/144 (9.7%) patients with CAPA, mean age was 50.35 (SD 11.9), the median time from admission to CAPA was 8 days; 28.5% received tocilizumab and 30‐day mortality was 57%. ROC analysis and Youden index identified 2.0 OD as the best cut‐off, resulting in sensitivity and specificity of 57.1% and 81.5% for GM‐EIA and 60% and 72.6% for GM‐LFA, respectively. Conclusions: The diagnostic performance of GM in tracheal aspirates improved after using a cut‐off of 2 OD. Although bronchoalveolar lavage testing is the ideal test, centres with limited access to bronchoscopy may consider this approach to identify or rule out CAPA.